Evaluation of pulsed electric fields technology for the improvement of subsequent carotenoid extraction from dried Rhodotorula glutinis yeast. (1st September 2020) - Martínez, J.M.; Schottroff, F.; Haas, K.; Fauster, T.; Sajfrtová, M.; Álvarez, I.; Raso, J.; Jaeger, H.
Highlights: PEF and subsequent aqueous incubation improved carotenoid extraction from dried yeast. PEF triggers effects occurring during incubation beyond membrane electroporation. Ethanol was the most efficient solvent, recovering 80% of carotenoid content. Torularhodin esters constituted the main carotenoid found in the extracts. Abstract: This research aims to evaluate whether the electroporation of Rhodotorula glutinis fresh biomass improved the subsequent extraction of carotenoids from dry biomass using supercritical CO2 and traditional solvent extraction. Supercritical CO2 extraction yields were low after all treatments assayed. Similarly, solvent extraction of carotenoids from untreated or PEF treated cells that were immediately freeze-dried after the pre-treatment was neither effective (extraction yield < 20% total content). Conversely, PEF-treatment and subsequent intermediate incubation in aqueous buffer for 24 h, followed by freeze-drying and extraction, led to a large improvement with the three solvents assayed (acetone, hexane, ethanol). Ethanol was the most efficient, reaching an extraction yield of 80% of total carotenoid, which represents a recovery of 267 µg/gdw . Torularhodin esters constituted the main carotenoid found in the extracts. This is of great interest, as ethanol is eco-friendly solvent and potential applications of torularhodin range from food to medical purposes.